MIGRATION PROCESSES ASSOCIATED WITH THE DEVELOPMENT OF THE BESHKOTON MASSIVE - Sirojiddin Kulboshev (Scholar Express Journal, 2023)
In order to satisfy the need for cotton, the Soviet government was actively implementing measures to develop reserves and gray lands. As one of these actions, the main attention was paid to the Surkhan-Sherabad deserts. In particular, measures for the development of the Beshkoton massif, which is part of the Surkhan-Sherabad deserts, were carried out rapidly. The development of the Beshkoton massif was extended to the population who voluntarily moved to the desert for the purpose of developing the desert along with the policy of forced relocation of the population living in the mountainous regions. For example, in 1954, the inhabitants of the villages of Boysun, Darband, Khojango, Khojabolgan, and Machai were relocated in order to develop the Sherabad-Beshkoton desert. The purpose of this relocation was to increase cotton production and expand new lands
Keywords: Soviet; government; goal; reserve